2014
DOI: 10.4103/0019-5545.140632
|View full text |Cite
|
Sign up to set email alerts
|

Indian Psychiatric Society multicentric study: Prescription patterns of psychotropics in India

Abstract: Background:There is a lack of national level data from India on prescription of psychotropics by psychiatrists.Aim and Objective:This study aimed to assess the first prescription handed over to the psychiatrically ill patients whenever they contact a psychiatrist.Materials and Methods:Data were collected across 11 centers. Psychiatric diagnosis was made as per the International Classification of Diseases Classification of Mental and Behavioural Disorders 10th edition criteria based on Mini International Neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 60 publications
7
18
2
Order By: Relevance
“…Morbidity pattern among psychiatric disorders showed substance-related disorders (28.71%) as the most common psychiatric disorder followed by schizophrenia and other psychotic disorders (22.77%). This is in contrary to the multicentric study conducted by the Indian Psychiatric Society where affective disorders followed by neurotic, stress-related, and somatoform disorders were the most common diagnostic categories [13]. Higher prevalence of substance use disorders in the present study may be probably due to increase help-seeking behavior for the same in the study population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Morbidity pattern among psychiatric disorders showed substance-related disorders (28.71%) as the most common psychiatric disorder followed by schizophrenia and other psychotic disorders (22.77%). This is in contrary to the multicentric study conducted by the Indian Psychiatric Society where affective disorders followed by neurotic, stress-related, and somatoform disorders were the most common diagnostic categories [13]. Higher prevalence of substance use disorders in the present study may be probably due to increase help-seeking behavior for the same in the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…This is similar to the results from the preliminary survey on antipsychotic prescribing pattern conducted among Indian Psychiatrists [15]. The most commonly prescribed antidepressant medication according to our study was escitalopram (57.40%) followed by sertraline (12.96%) which was similar to the findings from a multicentric study conducted by the Indian Psychiatry Society [13]. However, among the mood stabilizers, lithium and sodium valproate were commonly prescribed, followed by carbamazepine which is in contrary to study conducted by the Indian Psychiatry Society and in concordance with the study conducted by Trivedi et al [13,16].…”
Section: Discussionsupporting
confidence: 90%
“…In our study among atypical antipsychotics, Olanzapine was the most commonly prescribed agent, Our findings closely matches with study of Grover S et al [23,27] The benefit of Olanzapine may be due to its greater efficacy, noticeable improvement of negative symptoms, higher response rate, better maintenance of treatment, and finally lower incidence of adverse effects [28] Typical antipsychotic drugs accounts for 17.79 % of total antipsychotic drug prescriptions indicating that they still play an important role in Schizophrenia and offer a valid alternative to atypical where atypical drugs are poorly tolerated or where typical are preferred by patients themselves.…”
Section: Drug Utilization Pattern Of Psychotropic Drugs Prescribed Insupporting
confidence: 92%
“…[21] In a multicentric study conducted by Grover S et al [23] and Avasthi A et al [31] the most common mood stabilizer prescribed was Valproate . The overall prescribing frequency of Lithium was 1.3% while during the study.…”
Section: [29]mentioning
confidence: 99%
“…Clonazepam use was highest (56.47%), followed by lorazepam (40.6%) in the 1, 4 BNZ group and the only 1, 5 BNZ used was Clobazam. Grover et al 23 in their multicentre study found that among the benzodiazepines clonazepam was most popularly used (64%), followed by lorazepam (14.3%). Similar findings were reported by Rode et al 8 , namely 51.83% for clonazepam and 32.32% for lorazepam.…”
Section: Anxiolytic and Hypnotic Prescribing Patternmentioning
confidence: 99%